2016
DOI: 10.1007/s00383-016-3857-6
|View full text |Cite
|
Sign up to set email alerts
|

5 years after an ACE: what happens then?

Abstract: Overall 86% achieved excellent clinical outcome with 74% of patient still using their ACE at 5 years. HD has the highest recovery rate of 50%. FC has a more unreliable clinical outcome with 21% recovered colonic function and 21% failed. Outcome varied dependent on the background diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Dolejs et al reported 43% of patients were able to become independent from ACE flush with at least 24-month follow-ups [ 27 ]. Others had less promising outcomes, with 74% of patients still using their ACEs 5 years after the ACE procedure [ 28 ]. Rodriguez et al reported that in 64% of patients with constipation, the frequency of antegrade flushes could be decreased, while 28% successfully discontinued ACE administration at a 2-year (14–74 months) follow-up [ 11 ].…”
Section: Antegrade Continence Enemasmentioning
confidence: 99%
“…Dolejs et al reported 43% of patients were able to become independent from ACE flush with at least 24-month follow-ups [ 27 ]. Others had less promising outcomes, with 74% of patients still using their ACEs 5 years after the ACE procedure [ 28 ]. Rodriguez et al reported that in 64% of patients with constipation, the frequency of antegrade flushes could be decreased, while 28% successfully discontinued ACE administration at a 2-year (14–74 months) follow-up [ 11 ].…”
Section: Antegrade Continence Enemasmentioning
confidence: 99%
“…In all, the majority of patients with true incontinence after pullthrough-due to either damage to the anal canal mucosa or to the muscular sphincter mechanism-will require enema therapy for social continence. Antegrade continence enemas offer a favorable quality of life, and for patients with HD in particular, some will obtain recovery of continence and ability to wean off of enemas (29). Another promising option for social continence is the Peristeen integrated transanal irrigation system (Coloplast, Denmark), which may allow highly compliant children to avoid a surgical antegrade enema access procedure while providing a favorable quality of life (30).…”
Section: The Soiling Patientmentioning
confidence: 99%
“…[8][9][10][11][12] It is interesting that some of the papers mention that a subset of patients stopped using their ACE because of restoration of normal bowel movements after a period of time flushing the colon. 10,13 This finding makes us think that chronic constipation can get better once withholding behavior or pelvic floor dyssynergia (they can train their pelvic floor when doing a flush to evacuate it) is improved, or that the underlying motility disorder can change over time when the colon is flushed daily. Some data exist that might support this theory.…”
Section: Ileostomymentioning
confidence: 99%
“…This suggests that colonic dysmotility may not only contribute to the etiology of FC but may also be a consequence of long-standing FC, possibly because of fecal stasis leading to suboptimal colonic motor function. 10,[13][14][15][16][17][18] Sacral Nerve Stimulation Sacral nerve stimulation (SNS) involves low-amplitude electrical stimulation of the sacral nerves. This effect can be administered via transcutaneous stimulation of the posterior tibial nerve, transabdominal stimulation, or via an electrode placed through the sacral foramen.…”
Section: Ileostomymentioning
confidence: 99%
See 1 more Smart Citation